Outcomes and Health Care Resource Utilization of Adult Bacterial Meningitis in the United States. Issue 2 (April 2021) - Kiyani, Musa; Hodges, Sarah E.; Adil, Syed M.; Charalambous, Lefko T.; Liu, Beiyu; Lee, Hui-Jie; Parente, Beth; Perfect, John R.; Lad, Shivanand P.
Abstract : Objective: To examine the longitudinal health care resource utilization, in-hospital mortality, and incidence of downstream complications of bacterial meningitis in the United States. Methods: Using IBM MarketScan, we retrieved data on adult patients with a diagnosis of bacterial meningitis admitted to a US hospital between 2008 and 2015. Patients were stratified into groups (1) with/without prior head trauma/neurosurgical complications, (2) nosocomial/community acquisition, and (3) Gram-negative/positive bacteria. Cost data were collected for up to 2 years and analyzed with descriptive statistics and longitudinal modeling. Results: Among 4, 496 patients with bacterial meningitis, 16.5% and 4.6% had preceding neurosurgical complications and head injuries, respectively. Lumbar punctures were performed in 37.3% of patients without prior trauma/complications who went on to develop nosocomial meningitis, and those with prior head injuries or complications had longer initial hospital stays (17.0 days vs 8.0 days). Within a month of diagnosis, 29.2% of patients with bacterial meningitis had experienced downstream complications, most commonly hydrocephalus (12.7%). The worst 30-day mortality was due to tuberculous (12.3%) and streptococcal meningitis (7.2%). Overall, prior head trauma and complications were associated with higher costs. Community-acquired bacterial meningitis had lower median baseline costs relative to the nosocomial group (no head trauma/complication: $17, 152 vs $82, 778; head trauma/complication: $92, 428 vs $168, 309) but higher median costs within 3 months of diagnosis (no head trauma/complication: $47, 911 vs $34, 202; head trauma/complication: $89, 207 vs $58, 947). All costs demonstrated a sharp decline thereafter. Conclusions: Bacterial meningitis remains costly and devastating, especially for those who experience traumatic head injuries or have a complicated progress after neurosurgery.